2016
DOI: 10.1007/s11136-016-1475-3
|View full text |Cite
|
Sign up to set email alerts
|

Congruence between polysomnography obstructive sleep apnea and the pediatric sleep questionnaire: fatigue and health-related quality of life in juvenile idiopathic arthritis

Abstract: Purpose To examine the congruence between polysomnography obstructive apnea hypopnea index (OAHI) and parent reported obstructive sleep apnea (OSA) symptoms in 6-to-11 year-old children with juvenile idiopathic arthritis (JIA) and controls; and to compare fatigue and quality of life in JIA and control children based on OAHI and OSA symptoms. Methods Sixty-eight children with JIA and 75 controls and a parent participated. Children underwent one night of polysomnography in a sleep laboratory. Parents completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Arens et al found that the upper airway cross sectional area varies along the centerline between children with OSA and healthy controls with significant airway narrowing occurring continuously throughout most of the length of the upper airways in the OSA group. Arens et al speculated that the continuous narrowing of the upper airways may be essential to the air flow resistance that characterizes subjects with OSA [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arens et al found that the upper airway cross sectional area varies along the centerline between children with OSA and healthy controls with significant airway narrowing occurring continuously throughout most of the length of the upper airways in the OSA group. Arens et al speculated that the continuous narrowing of the upper airways may be essential to the air flow resistance that characterizes subjects with OSA [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…OSA is at the extreme end of the manifestation of SDB and has received attention in JIA research [ 32 , 33 ]. OSA is characterized by increased upper airway resistance causing partial (hypopnea) or complete collapse (apnea) of the upper airways followed by increased respiratory efforts, arousals, and sleep fragmentation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…PSG is usually conducted in a specialized hospital sleep laboratory and is typically limited to a single overnight assessment. There are some limited data on PSG to assess sleep in youth with [ 27 ] chronic pain, mostly in small samples with rheumatological conditions [ 28 , 29 ], and it is not yet clear how PSG may help with the evaluation or management of sleep complaints in youth with chronic pain.…”
Section: Approaches For Sleep Health Assessment In Pediatric Pain Pop...mentioning
confidence: 99%
“…Fatigue is associated with significant distress and psychological disability and is a frequent reason for adolescents presenting to primary medical services [13,43]. Fatigue is frequently among the most distressing symptoms associated with a range of paediatric medical conditions [26] including cancer [46], primary immunodeficiencies [50], paediatric-onset multiple sclerosis [57], lupus [18], and juvenile idiopathic arthritis [66] contributing to poorer healthrelated quality of life [19]. Tasks that produce fatigue have been demonstrated to increase pain in people with fibromyalgia [15].…”
Section: Introductionmentioning
confidence: 99%